Analisis Implementasi Kebijakan Zakat Sebagai Pengurang Penghasilan Kena Pajak Wajib Pajak Orang Pribadi Pada Kantor Lazismu Di Jakarta Pusat Tahun 2018 - Abdul Rahmat; Johansyah Zaini (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
This study aimed to analyze the implementation of the zakat policy as a reduction of taxable income of individual taxpayers at the LAZISMU office in Central Jakarta in 2018, and also to analyze the inhibiting entities faced, as well as the driving entities for LAZSIMU office in implementing the zakat policy as a reduction of taxable income of individual taxpayers. This research used a descriptive qualitative approach. The results showed that the implementation of the zakat policy as a reduction of taxable income of individual taxpayers at the LAZISMU office in Central Jakarta in 2018 according to the six factors used by the writer, policy size and objectives, resources, communication between organizations, character of implementing agents, disposition (tendencies/attitudes) of implementers, social, economic and political environments have been fulfilled. However, there are still some obstacles faced by LAZISMU in implementing the zakat policy as a reduction of taxable income, such as size and policy objectives, social and political environmental conditions, and support and participation of taxpayers in supporting this policy. Therefore the government must evaluate and overcome the obstacles in the implementation of the zakat policy as a reduction of taxable income.